Analisis Kualitas Pelayanan Dan Kepuasan Pengunjung Wisata Di Desa Wisata Cibuntu Kabupaten Kuningan (Diagram Kartesius) - Rianto Rianto (Program Studi Hospitality dan Pariwisata, 2017)
This study aims to determine whether the dimensions of service quality that is tangible, reliability, responsiveness, assurance, and empathy that has been given to the satisfaction masyarakay Cibuntu Village Tourism Village visitors Cibuntu. The population in this study were the guests who visited the village Cibuntu to do sightseeing. Samples were taken of 200 respondents using Non-Probability Sampling technique using tables in Sugiono Isaac and Michael (2014), in which the sample was taken 10% of the total population of 2012, which visitors coming period of 2012 s / d in 2014. Based on the results of research known of the five dimensions of service after inserted into the Cartesian diagram of the dimensions of responsiveness (responsiveness) included in quadrant A (Priority), which means that this dimension is still considered less well and have not been able to satisfy pengunjung. For realibility dimensions, assurance, tangible, empathy included in quadrant B (Maintain Achievement), which means that the fourth dimension is considered good and had satisfactory pengunjung.Berdasarkan these results, it is necessary in the training held on the responsiveness of the community in providing pekayanan to visitors at the Tourism Village Cibuntu, so the service given to the visitor can give satisfaction.Keywords: service quality, tangible, reliability, responsivenes, assurance, emphaty , customer satisfaction, tourism village